A case study: promoting on halal integrity among SMEs through training by Halal Industry Development Corporation (HDC) / Nornadiah Mohd Salleh - Mohd Salleh, Nornadiah (Faculty of Business and Management, 2010)
Malaysia is a progressive Islamic country. It is business-friendly to Muslims and non-Muslims alike, making it a halal industry advantage. With a stake in commercial sectors worldwide, Halal Development has become a significant contributor to all facets of economic growth. The target to become halal hub, that’s why Halal Industry Development Corporation (HDC) was established. HDC’s role is to unite the national halal industry players to form the basis of a global halal community. However, people’s awareness towards halal Malaysia is still low. The focus of this study is to promoting Halal Integrity among SMEs through training that elevates the knowledge of halal better. The data was collected through surveys, questionnaire and journals. After the conclusion has been made, a few recommendations were brought up with hope to improve the level of awareness on Halal Integrity among SMEs in the future.